Kontribusi Manajemen Strategik dan Sumber Daya Manusia terhadap Daya Saing Sekolah - Kuntum Khaira; Zulfani Sesmiarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of strategic management and human resources to school competitiveness. The competitiveness of educational institutions is a crucial factor in facing global competition, particularly in non-formal educational institutions such as Community Learning Centers (PKBM). This study is motivated by the importance of effective organizational strategic management and the development of quality human resources in enhancing school competitiveness. The research method used is a quantitative approach with data collection techniques through questionnaires, interviews, and observations. This study was conducted at PKBM schools in Bukittinggi City, involving educators and administrators as respondents. Data analysis was conducted using statistical techniques to examine the relationship and contribution of strategic management and human resources variables to school competitiveness. The results of the study indicate that strategic management and human resources have a significant contribution to school competitiveness. Effective strategic management can improve the direction and objectives of the organization clearly, while good quality human resources play a role in increasing productivity, innovation, and the quality of educational services. In addition, the synergy between strategic planning and human resource management is a key factor in creating sustainable competitive advantage. The conclusion of this study is that increasing school competitiveness can be achieved through strengthening strategic management and sustainable human resource development. Therefore, educational institutions need to optimize both aspects as part of a strategy to improve quality and competitiveness in the era of globalization.